Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Hi there!
We can use implicit differentiation with respect to x:
[tex]3xy = 4x + y^2[/tex]
If a term with 'y' is differentiated, a 'dy/dx' must be included.
We can differentiate each term separately for the explanation.
3xy
We must use the power rule since 'x' and 'y' are both in this term.
Power rule:
[tex]f(x) * g(x) = f'(x)g(x) + g'(x)f(x)[/tex]
[tex]3xy \\\\f(x) = 3x\\g(x) = y \\\\f'(x)g(x) + g'(x)f(x) = 3y + 3x\frac{dy}{dx}[/tex]
Now, we can do the others.
4x
This is a normal power rule derivative.
[tex]f(x) = 4x\\f'(x) = 4[/tex]
y²
Since we are not differentiating with respect to y, we must include 'dy/dx'.
[tex]f(x) = y^2\\f'(x) = 2y\frac{dy}{dx}[/tex]
Combine the above:
[tex]3y + 3x\frac{dy}{dx} = 4 + 2y\frac{dy}{dx}[/tex]
Rearrange to solve for dy/dx.
Move dy/dx to one side:
[tex]3x\frac{dy}{dx} - 2y\frac{dy}{dx} = 4 + 3y \\\\[/tex]
Factor out dy/dx and divide:
[tex]\frac{dy}{dx}(3x- 2y) = 4 + 3y \\\\\boxed{\frac{dy}{dx} = \frac{4+3y}{3x-2y}}[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.